2017
DOI: 10.3892/mmr.2017.7497
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 induces caveolin-1 degradation and impaired mitochondrial function in E11 podocytes

Abstract: Increased intercellular reactive oxygen species (ROS) levels are the major cause of podocyte injury with proteinuria. Caveolin‑1 (CAV‑1) is an essential protein component of caveolae. CAV‑1 participates in signal transduction and endocytic trafficking. Recent research has indicated that CAV‑1 regulates oxidative stress‑induced pathways. The present study used hydrogen peroxide (H2O2) at nontoxic concentrations to elevate the level of ROS in E11 podocytes. Treatment with 500 and 1,000 µM H2O2 for 1 h significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Although we found no change in podocyte catalase expression by H 2 O 2 , others noted it either decreased (Y.‐H. Chen, Lin, Liu, & Su, ) or increased (Lu et al, ). Interestingly, patients with catalase gene mutation have life‐long increased H 2 O 2 concentration, which has cytotoxic effects on pancreatic cells, to be a risk factor for diabetes (Goth, ).…”
Section: Discussioncontrasting
confidence: 72%
“…Although we found no change in podocyte catalase expression by H 2 O 2 , others noted it either decreased (Y.‐H. Chen, Lin, Liu, & Su, ) or increased (Lu et al, ). Interestingly, patients with catalase gene mutation have life‐long increased H 2 O 2 concentration, which has cytotoxic effects on pancreatic cells, to be a risk factor for diabetes (Goth, ).…”
Section: Discussioncontrasting
confidence: 72%
“…And mitochondrial dysfunction is considered as a hallmark of intrinsic apoptosis. In E11 podocytes, cav-1 OE attenuated H 2 O 2 -induced oxidative stress responses and preserved mitochondrial function, as well as significantly suppressing apoptosis [153]. Moreover, various cav-1-deficient cells have displayed mitochondrial dysfunction including impaired energy generation, and increased mitochondrial ROS production [154156].…”
Section: Important Role Of Cav-1 In Ismentioning
confidence: 99%
“…In addition to previously mentioned functions, several studies have found that Cav1 may also be related to stress-induced premature senescence in a biphasic manner. Initially, it appeared that Cav1 can be induced by sub-cytotoxic levels of H 2 O 2 , to accelerate premature senescence and mitochondrial dysfunction [182][183][184][185] ; however, when Cav1 expression is inhibited either in Cav1-null mice, or by using antisense Cav1, premature senescence by H 2 O 2 does not occur. [182,186] Recently, it has also been shown that strong suppression of Cav1 induces premature senescence in a p53-p21-dependent manner.…”
Section: Role Of C Av1 In Cellul Ar S Ene Scen Ce and S K In Ag Eingmentioning
confidence: 99%